SEBUAH ULASAN SINGKAT TENTANG BETON AGREGAT DAUR ULANG - DANANG HADI NUGROHO; HADI SURYA WIBAWANTO SUNARWADI; HERU PRASETYO NUGROHO (JURNAL DAKTILITAS, 2024)
Abstract This paper briefly introduces the recycling and regeneration preparation of waste concrete, as well as the crushing and screening process of waste concrete blocks. The properties of crushed aggregate and the physical and mechanical properties of recycled concrete were analyzed, and the research status of compressive strength and splitting tensile strength of waste concrete at home and abroad was summarized and analyzed. Factors such as water-glue ratio, water absorption, apparent density of recycled coarse aggregate, state of recycled coarse aggregate and strength of virgin concrete will affect the strength of recycled aggregate concrete. This paper also summarizes the relationship between the splitting tensile strength of recycled aggregate concrete and the compressive strength of the cube. Keywords: Recycled aggregate concrete; compressive strength; splitting tensile strength. Abstrak Makalah ini secara singkat memperkenalkan persiapan daur ulang dan regenerasi limbah beton, serta proses penghancuran dan penyaringan blok beton limbah. Sifat agregat hancur dan sifat fisik dan mekanik beton daur ulang dianalisis, dan status penelitian kuat tekan dan kuat tarik belah beton limbah di dalam dan luar negeri dirangkum dan dianalisis. Faktor-faktor seperti perbandingan water-glue, daya serap air, berat jenis agregat kasar daur ulang, keadaan agregat kasar daur ulang dan kekuatan beton perawan akan mempengaruhi kekuatan beton agregat daur ulang. Tulisan ini juga merangkum hubungan antara kuat tarik belah beton agregat daur ulang dengan kuat tekan kubus. Kata kunci: Beton agregat daur ulang; kekuatan tekan; kekuatan tarik belah.